Clonal transmission and species-specific mechanisms of polymyxin resistance in carbapenem-resistant Enterobacteriaceae from Southwest China - Si, Tingting; Liu, Hang; Xia, Peiwen; Huang, Na; Tang, Shiyu; Li, Yuqiong; Han, Qi; Song, Yuanyuan; Liu, Yingyi; Xia, Yun (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectivesThe rapid dissemination of carbapenem-resistant Enterobacteriaceae (CRE) poses a severe global health threat due to limited treatment options. Polymyxin is currently considered a last-resort therapy for human infections caused by CRE. The increasing clinical use of polymyxin has resulted in alarming resistance rates. This study investigated the clinical characteristics, molecular epidemiological characteristics, and resistance mechanisms of polymyxin-resistant CRE (PR-CRE) in Chongqing, China.MethodsAntimicrobial susceptibility and resistance genes were analyzed by PCR-based amplification and sequence analysis. Molecular epidemiological characteristics were analyzed using Enterobacterial Repetitive Intergenic Consensus (ERIC)-PCR and multilocus sequence typing (MLST). The gene expression of pmrC and pmrK was analyzed using qRT-PCR. Conjugation experiments were performed to determine plasmid transferability. Whole-genome sequencing (WGS) was performed to analyze their genetic environment.ResultsThirty PR-CRE isolates, including 21 Klebsiella pneumoniae and 9 Escherichia coli, exhibited multidrug resistance, with three pan-resistant K. pneumoniae strains. The predominant lineage was ST11-K64 K. pneumoniae (n=14/21), with four genetically identical isolates from ICUs, confirming clonal transmission. In contrast, all E. coli displayed high genetic diversity. Hypervirulence determinants were detected in 38.1% (n=8/21) of K. pneumoniae. Two rare K. pneumoniae strains were identified: one hypervirulent ST3984-KL64 strain co-harboring blaKPC-2 and blaNDM-1, and one ST2383-KL81 strain harboring blaOXA-48. Species-specific resistance mechanisms emerged: K. pneumoniae relied on chromosomal mutations in mgrB, phoPQ, and pmrAB, especially mgrB inactivation (57.1%, n=12/21) via ISKpn26/IS903B/ISAeme19/ISKpn14 and pmrK upregulation (95.2%, n=20/21), while E. coli exclusively used plasmid-borne mcr-1 with 55.6% (n=5/9) conjugation efficiency, conferring low-level resistance. Genomic sequencing revealed that four identical ISAeme19 copies were first identified in ST11-KL64 hypervirulent CRKP-5: two on the chromosome (mgrB and kdsD), and two on plasmids (IncFII/IncR pkp2007-KPC and recombinant pkp2007-D). Transposition of ISAeme19 from pkp2007-KPC to mgrB was evidenced by the inverted orientation and matching flanking repeats. Crucially, a pan-resistant ST11-KL64 K. pneumoniae harbored a fusion plasmid with dual blaKPC-2 and catA2 copies bracketed by IS26, a previously unreported configuration. Additionally, four novel deleterious mutations were detected: mgrB-Asn25Thr, phoP-Lys199Met, phoQ-Tyr89His, and RamR-Ala17Thr.ConclusionThese findings reveal species-divergent resistance mechanisms to polymyxin, necessitating enhanced surveillance of these high-risk clones, mobile elements, and emergent resistance mechanisms.